2021
DOI: 10.1074/jbc.ra120.014793
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-specific BMP and activin membrane-bound inhibitor (BAMBI) deletion promotes adipogenesis by accelerating ROS production

Abstract: With the improvement of people's living standards, the number of obese patients has also grown rapidly. It is reported that the level of oxidative stress in obese patients has significantly increased, mainly caused by the increase in reactive oxygen species (ROS) levels in adipose tissue. Studies have shown that the use of siRNA to interfere with BMP and Activin Membrane-Bound Inhibitor (BAMBI) expression could promote adipocyte differentiation, and under hypoxic conditions, BAMBI could act as a regulator of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…A recent study showed that adipocyte-specific depletion of BAMBI caused an induction of Nox4 expression in adipose tissue, thereby promoting ROS generation in cytoplasm and mitochondria. The deficiency of BAMBI in adipose tissue resulted in an enhanced DNA-binding activity of C/EBPβ and promoted adipogenesis ( 154 ). These results together suggested that BAMBI may be an important mediator of adipogenesis through regulating ROS.…”
Section: Potential Targets Mediating Oxidative Stress In Adipose Tissmentioning
confidence: 99%
“…A recent study showed that adipocyte-specific depletion of BAMBI caused an induction of Nox4 expression in adipose tissue, thereby promoting ROS generation in cytoplasm and mitochondria. The deficiency of BAMBI in adipose tissue resulted in an enhanced DNA-binding activity of C/EBPβ and promoted adipogenesis ( 154 ). These results together suggested that BAMBI may be an important mediator of adipogenesis through regulating ROS.…”
Section: Potential Targets Mediating Oxidative Stress In Adipose Tissmentioning
confidence: 99%
“…Genetic and evolutionary analysis suggests that the increased expression of BMPR2 mRNA in adipose tissue of obese patients has been selected because it is a metabolic “thrifty” gene that is contributing to present day obesity [ 17 ]. Recent studies in mice showed that enhanced BMP activity causes obesity, hyperglycemia, and insulin resistance [ 18 , 19 ]. The mechanism by which overactive BMP signaling contributes to obesity is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Establishment of the mitochondrial network is the prerequisite for stem cells to differentiate into a functional phenotype (21,22). A previous study showed that interference with the expression of BMP and activin membrane-binding inhibitor (BAMBI) can promote the production of ROS in the cytoplasm and mitochondria along with the DNA binding activity of C/ EBPβ, to ultimately promote adipocyte differentiation and adipogenesis (23). Collectively, these data suggest that mitochondria may play a role in BMP5-regulated cell proliferation and differentiation.…”
Section: Introductionmentioning
confidence: 99%